Atentando-se ao mindfulness: uma revisão sistemática para análise dos conceitos, fundamentos, aplicabilidade e efetividade da técnica no contexto da terapia cognitiva - Castro, Filipe Silva (2014)
Spirituality and religiosity have become the subject of scientific interest on the health publications. Therefore, there was an openness to consider the religious practices. One of these is mindfulness that has been increasing studied. This technique is define as the awareness in the present moment, whatever arises internally or externally, without making judgments or desire for things to be different. The overall objective of this research was to perform a systematic literature review of scientific productions that address the mindfulness technique. Therefore, five databases were consult: PsycInfo, SCIELO Pepsic, LILACS and PsycARTICLES. In these, 35 articles were collect. Most of them were produce in American institutions and published in English. There is few studies published in Brazil or in Portuguese about mindfulness. The articles was in two forms: as a theoretical paper (46 %) or as a randomized study (54 %). It found that the technique was consider as an important feature in the reduction of stress, feelings of distress, in reducing the symptoms of burnout, in the management of chronic pain and control symptoms of panic. The studies are heterogeneous and show improvements in samples of patients with cancer, depression, anxiety disorder, borderline disorder. Another objective was to discuss how mindfulness was propose in different therapies such as Acceptance and Commitment Therapy (ACT), Dialectical Behavioral Therapy (DBT) and Mindfulness-Based Cognitive Therapy (MBCT). In such approaches, mindfulness listed as a key to the therapy fully occur and reach the proposed result. In studies involving MBCT, there was indication of improving treatment of depression relapse. The MBCT was effective as a treatment for people with depression, anxiety and as a resource in reducing stress. In studies with ACT, the treatment was effective for generalized anxiety disorder and as a complement in the treatment of other conditions. This study also examined the interview by Donna Sudak to discuss how the technique has been seen, used and which parameters are being observed. The definitions provided by Donna Sudak and by the Tibetan leader Dalai Lama (14º) were compared on mindfulness, discussing the differences in the design of mindfulness in the scientific and religious context. Donna Sudak focused mindfulness as a technique that could be learn regardless of religious values that the individual has, and suggesting that the recommendation should be according to the patient\'s need. Dalai Lama defined mindfulness as a meditation and Buddhist tradition, which from observation and awareness of the mind allows us to observe, accept and change thoughts. In general, therapeutic approaches have proposed the concept and application of the technique similar to the way Buddhism and although the final interest is different, the technique has shown good results effectively in relation to well- being and health. Thus, studies emphasize that mindfulness may be an important therapeutic tool for cognitive- behavioral therapists.